Green Purchase: A Systematic Review and Future Research Agenda - Setyo Ferry Wibowo; Mukhamad Najib; Ujang Sumarwan; Yudha Heryawan Asnawi (School of Business, IPB University (SB-IPB), 2022)
The purpose of this paper is to provide a holistic understanding of the contexts and theories applied in green purchase behavior studies. This research used PRISMA's systematic review method to analyze 76 empirical articles on green purchase intention and behavior from 2014 to 2019 across countries. This research is one of the first studies to cross-examine the context and theories applied in green purchase studies. For each theory applied, we present a brief description and recommendation for the future agenda of research agenda. Despite the breadth of previous studies' results, this review indicates that most studies investigated green products in general. Furthermore, the theory of planned behavior, the theory of perceived value, and the theory of personal value emerged as the three main theoretical frameworks of consumer green purchase behavior study across products and countries. The paper will help policymakers and managers formulate and implement strategies to encourage green purchasing and give insight into the future direction of green purchase study. Keywords: systematic review, green purchase, green products, theoretical framework